Land Transport and the South Australian Copper and Smelting Industries, 1845-1870 - Davies, Melville (Revista de Historia Social y de las Mentalidades, 2024)
This article analyses the transformations in land transport during the period 1845-1870 in Chile and Southern Australia. The use of oxen and mules, carts and muleteers as the main means of transport remained important despite the introduction of the railway opportunity costs and the heavy investment demanded by the development of a modern infrastructure meant that traditional means of transport were a viable alternative. Through the analysis of business records about the transport of minerals from foundries to ports this article endeavors to study the actors and their preference for traditional means of transportation.